MODERN ASPECTS OF SUPPOSITORIES MANUFACTURING - N. B. Diomina (Разработка и регистрация лекарственных средств)
The article gives an overview of the modern aspects in the production of suppositories. The nomenclature and brief description of excipients that used in the composition of suppositories were described. There were also reviewed the typical equipment for production of mentioned dosage form (DF), pharmacopoeial principles for regulation of quality and various instruments for its evaluation.